2016
DOI: 10.1016/j.tranon.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Droxinostat, a Histone Deacetylase Inhibitor, Induces Apoptosis in Hepatocellular Carcinoma Cell Lines via Activation of the Mitochondrial Pathway and Downregulation of FLIP

Abstract: Background: The current chemotherapeutic outcomes for hepatocellular carcinoma (HCC) are not encouraging, and long-term survival of this patient group remains poor. Recent studies have demonstrated the utility of histone deacetylase inhibitors that can disrupt cell proliferation and survival in HCC management. However, the effects of droxinostat, a type of histone deacetylase inhibitor, on HCC remain to be established. Methods: The effects of droxinostat on HCC cell lines SMMC-7721 and HepG2 were investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…5d ). A previous study showed that droxinostat decreased the expression of c-FLIP [ 28 , 29 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5d ). A previous study showed that droxinostat decreased the expression of c-FLIP [ 28 , 29 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of c-FLIP was decreased by droxinostat treatment in HT-29 cells, which resulted in the activation of the extrinsic apoptotic pathway. Waugh et al and Zhang et al also found that HDACIs, such as droxinostat and SAHA, downregulated c-FLIP expression in prostatic cancer cells and hepatocellular carcinoma cells [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 Droxinostat, a type of histone deacetylase inhibitor, suppresses HDAC3 expression and induces histone acetylation and HCC cell death through activation of the mitochondrial apoptotic pathway and downregulation of FLIP, supporting its potential application in the treatment of HCC. 7 A recent study reported that HDAC3 participates in hepatitis C virus (HCV) replication, and RGFP966 may be a potential treatment for diseases associated with HCV infection such as HCC, although no change in cell viability following treatment of 10μM RGFP966 in HCV-infected Huh7 cells. 20 In accordance with this report, we found that RGFP966 mildly inhibits cell proliferation of Huh7 and HepG2 cells at a higher concentration, whereas remarkable inhibitory effect was shown in PLC/PRF/ 5 cells following treatment of 10μM RGFP966 (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Histone deacetylases (HDACs) play major roles in diverse biological functions, and HDAC inhibitors show clinical promise for the treatment of cancers, including HCC. [6][7][8] Based on sequence similarity, HDAC family are divided into four subfamilies: classes I, IIa, IIb, III, and IV. HDAC3 was the third one to be identified of HDACs and belongs to class I HDACs.…”
Section: Introductionmentioning
confidence: 99%
“…Droxinostat, a HDAC inhibitor, was found to suppress HDAC3 expression and induce acetylation of histones H3 and H4. This compound can inhibit cell proliferation and induce apoptosis in HCC cell lines by activating mitochondrial apoptotic pathways (31). A novel histone deacetylase inhibitor, MPT0G009 was reported to be a potential new candidate drug for HCC therapy.…”
Section: Applications Of Hdac Inhibitor For the Therapy Of Hccmentioning
confidence: 99%